Association Between Preinjury Symptoms and Postconcussion Symptoms at 4 Weeks in Youth. Issue 2 (March 2022) - Ledoux, Andrée-Anne; Tang, Ken; Gagnon, Isabelle; Osmond, Martin H.; Yeates, Keith O.; Healey, Katherine; Gioia, Gerard A.; Zemek, Roger L.
Abstract : Objective: To investigate whether preinjury physical, emotional, cognitive, and sleep symptoms on the Post-Concussion Symptoms Inventory (PCSI) are associated with persistent postconcussion symptoms (PPCS) at 4 weeks and whether any associations are moderated by sex or age. Study Setting and Participants: A total of 3063 participants with acute concussion, presenting to 9 Canadian pediatric emergency departments, were enrolled from August 2013 to June 2015. Design: A planned secondary analysis of a prospective, multicenter cohort study (Predicting Persistent Post-concussive Problems in Pediatrics or 5P). Primary outcome was PPCS at 4 weeks, defined as 3 or more new or worsening individual symptoms compared with the preinjury score at 28 days on the PCSI. The association between preinjury scores and PPCS was analyzed with a multivariable logistic regression analysis that included preinjury, sex, age, sex × preinjury, and age × preinjury interactions as predictors. Missing baseline covariates were imputed. Results: A total of 2123 ( n = 844 [39.8%] girls; median [IQR] age = 12.9 [10.7, 15.0] participants were included in the analysis. Preinjury physical symptom score was associated with PPCS at 4 weeks (χ 2 = 13.87, df = 6, P = .031). The preinjury emotional score also contributed to the variability in PPCS (χ 2 = 11.79, df = 6, P = .067). While girls reported higher preinjury physical, emotional, and cognitive scores than boys, neither sex nor age interacted with preinjury to predict PPCS at 4 weeks. Independent of age and sex, preinjury physical symptoms were associated with PPCS at 4 weeks (OR = 1.40; 95% CI, 1.15-1.70). Conclusion: Preinjury physical symptoms are associated with the probability of having PPCS at 4 weeks postconcussion independent of age and sex. Providers should consider preinjury symptoms to inform prognosis and recovery management.